Spatial-Temporal Analysis of Ambient Air Quality in Karachi through Geostatistical Interpolation (IDW) Technique - Idress, Muhammad; Nergis, Yasmin; Afzal, Ambreen; Ahmed, Samreen Riaz; Vambol, Viola; Vambol, Sergij; Butt, Jawad Abdullah; Sharif, Mughal; Yeremenko, Sergiy (Journal of Environmental Accounting and Management, 2026)
The disastrous impact of climate change is already being felt around the globe. Climate change is affected by increasing discharges of greenhouse gases. Pakistan's metropolitan air pollution is among the utmost severe in the world and it bases main reparations on economic activities and affects human health. This study has been designed for the analysis of ambient air quality in different Karachi areas. The surveys have been done based on seasonal variation i.e., pre and post-monsoon from four industrial zones viz. S.I.T.E area, North Karachi industrial area, Korangi industrial area, and Landhi industrial area in the year 2019. These zones are com-prised of the industrial, residential, and commercial sectors, so heavy traffic and dense populations affect these zones. In this study, HAZ-SCANNER (HIM-6000) apparatus was used for data collection of Ambient air pollutants like nitrogen oxides (NOx), carbon monoxide (CO), and sulphur dioxide (SO$_{2}$), particulate matters (TSPM, PM$_{10}$, and PM$_{2.5}$). For spatial-temporal analysis of ambient air quality GIS interpolation (IDW) technique has been used. It is observed that in post-monsoon, the intensity of particulate matters (TSPM, PM$_{10}$ & PM$_{2.5}$), CO, and NO$_2$ values in sampling sites are less to moderate than the values of pre-monsoon due to the seasonal monsoon effects. While North Karachi is at the least risk because of having a small number of scale industries pre-sent. The PM$_{10}$ & PM$_{2.5}$ levels average about 2-3 fold greater than the SEPA standards. High levels of ambient air pollutants cause severe health problems and chronic diseases on human health. Therefore, the implementation of rules and regulations regarding ambient air pollutants should be more active.